2009
DOI: 10.1063/1.3137194
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of Al-doped Zn0.95Co0.05O films: Experiment and theory

Abstract: Al-doped ZnCoO films were grown by sol-gel process onto SiO2 and Si(100) substrates. Structural analysis shows that all samples have the hexagonal würtzite structure with a slight preferential orientation along the c-axis. The insertion of Al and Co into the ZnO matrix has been experimentally evidenced by UV-visible spectroscopy and transmission electron microscopy. This is further supported by x-ray photoelectron spectroscopy which indicated that all Co is under ionic form and that the samples contain no meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…For each spectrum, four Co 2p peaks are observed: the 2p 3/2 and 2p 1/2 doublet and the shake-up satellite peaks that are assigned to the presence of Co 2? ions [14]. The Co 2p 3/2 and 2p 1/2 binding energies are observed, respectively, at 780.6 and 796.3 eV for Zn 0.9 Co 0.1 O powder and at 780.7 and 796.3 eV for Zn 0.9 Co 0.1 O bulk ceramic.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…For each spectrum, four Co 2p peaks are observed: the 2p 3/2 and 2p 1/2 doublet and the shake-up satellite peaks that are assigned to the presence of Co 2? ions [14]. The Co 2p 3/2 and 2p 1/2 binding energies are observed, respectively, at 780.6 and 796.3 eV for Zn 0.9 Co 0.1 O powder and at 780.7 and 796.3 eV for Zn 0.9 Co 0.1 O bulk ceramic.…”
Section: Introductionmentioning
confidence: 88%
“…ZnO-based DMSs, in particular, are of great interest since it has been predicted that Mn-doped ZnO in p-type can be ferromagnetic with high Curie temperature over 300 K [2] and Co doping in n-type ZnO can also realize room-temperature (RT) ferromagnetism (FM) [3]. A considerable amount of experimental studies corresponding to ZnO-based DMSs, especially Co-doped ZnO, have been reported [4][5][6][7][8][9][10][11][12][13][14]. However, many experimental studies on Co-doped ZnO focus on the powder [4][5][6][7][8][9] or thin film [10][11][12][13][14] materials.…”
Section: Introductionmentioning
confidence: 99%
“…A number of researchers have successfully reported a Curie temperature T c higher than room temperature in many TM-doped ZnO samples [10,11]. On the contrary, many groups have failed to observe the room temperature ferromagnetism in these systems [12,13]. Experimentally, the prediction of high temperature ferromagnetism depends on a large number of experimental parameters: preparation methods, measurement techniques, substrate choice, unexpectedly carriers introduced during the synthesis, for example, H or O, and acceptor or donor defects.…”
Section: Introductionmentioning
confidence: 97%
“…ZnCo 2 O 4 , which is a spinel oxide with strong ferromagnetism and high Curie temperatures (Tc) greatly exceeding room temperature [13,[18][19][20] constitutes another class of ferromagnetic semiconductors. Although there are numbers of studies on cobalt doped ZnO [21][22][23][24][25][26], the ferromagnetism of n-type and p-type ZnCo 2 O 4 is a continuous debate and the microscopic origins of this ferromagnetism remain poorly understood. Moreover, there is no consensus on whether the observed ferromagnetism is intrinsic.…”
Section: Introductionmentioning
confidence: 98%